The feasibility of a purpose-renewal intervention after treatment for early stage breast cancer: A brief report. Issue 4 (3rd July 2020) - Radomski, Mary Vining; Swenson, Karen K.; Anheluk, Mattie; Zola, Joette; Kreiger, Rob; Rabusch, Stacey; Halsten, Jerry; Kath, Kristina; Carroll, Ginger; Zust, Barbara L.
Abstract: This feasibility study evaluated the acceptability, implementability, and preliminary efficacy of a brief purpose renewal intervention (the Compass Course) using a one-group pretest-posttest design. Fifteen women who had completed treatment for early-stage breast cancer enrolled in the study. Twelve completed the eight-session group intervention that was designed to help participants identify daily priorities (actual and aspired) that most align with their personal strengths, values, and sources of meaning, that is, their inner compass. The intervention was found to be acceptable and implementable. Preliminary pre- and post-intervention outcomes suggested that participants experienced greater purpose in daily life at posttest but that they did not make demonstrable changes in their activities or roles. Results suggest that the Compass Course was feasible and further study related to purpose renewal for adults with early-stage cancer is warranted.